Estudio seroepidemiológico de Neospora caninum en bovinos de traspatio en los cantones de Latacunga, La Maná y Salcedo de la provincia de Cotopaxi. - Toaquiza Enríquez, Sandy Lizbeth (2022)
The current research was carried out to study about seroepidemiology of the Neospora caninum in Latacunga, La Mana and Salcedo, cantons which are part of Cotopaxi province to establish its prevalence and the associated risks factors, for that reason an epidemiology survey was carried out which valued the age, breed, abortions and another existence symptoms in the female bovines, time of deworming and essentially the existence of canines were indispensable to take the sample. For this research 276 blood serum of female bovine of traspatio were taken, which were processed with CELISA technique in the parasitology laboratory of veterinarian clinic of Cotopaxi Technical University. The total of animals with the antibodies existence against Neospora caninum were 71 positives, which represent a prevalence of 25.7 % taking in account that there was not correlation between the seropositivity and risk factors, therefore that is concluded that the Canton with most prevalence corresponds to Salcedo Canton with a prevalence of 81%, without associate to the factors which were analyzed through the epidemiology survey. This parasitical sickness has a great impact in the livestock field by its main symptoms such as abortion, mummification, birth of weak fetus and over all the low milk production and the no-existence of a vaccine for its prevention, measures of prevention and monitoring should be taken in order to avoid the spread of the Neospora caninum parasite.